1996
DOI: 10.1677/joe.0.1490081
|View full text |Cite
|
Sign up to set email alerts
|

GH regulation of the Type 2 IGF receptor in regenerating skeletal muscle of rats

Abstract: GH enhances skeletal muscle growth, and IGF-II peptide is highly expressed during regeneration. We have therefore investigated the effect of GH administration on IGF-II binding and expression in regenerating rat skeletal muscle using the techniques of receptor autoradiography and in situ hybridisation. Notexin, a myotoxin, was injected into the right M. biceps femoris (day 0), causing affected fibres to undergo necrosis followed by rapid regeneration. Animals were administered either GH (200 micrograms/100 g b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Upregulation of myostatin expression concommitant with down-regulation of IGF-II expression has also been noted during muscle wasting (Shivji et al, 1999). Taken together, these studies and the present findings support a role for myostatin as a regulator of myoblast and satellite cell proliferation, and a role for IGF-II in the regulation of myoblast and satellite cell differentiation (Tollefsen et al, 1989;Kirk et al, 1996).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Upregulation of myostatin expression concommitant with down-regulation of IGF-II expression has also been noted during muscle wasting (Shivji et al, 1999). Taken together, these studies and the present findings support a role for myostatin as a regulator of myoblast and satellite cell proliferation, and a role for IGF-II in the regulation of myoblast and satellite cell differentiation (Tollefsen et al, 1989;Kirk et al, 1996).…”
Section: Discussionsupporting
confidence: 83%
“…In the current study, dw/dw rats undergoing muscle fibre necrosis and regeneration following notexin (a potent myotoxin) injection in the M. biceps femoris were administered exogenous GH in order to enhance the muscle regeneration process. Previously we have shown that GH-treatment of the dw/dw rats from this study increased muscle weight but did not alter regeneration time (Kirk et al, 1996). Further, we identified an increase in IGF-II message associated with regenerating muscle which was not affected by GH-administration.…”
supporting
confidence: 56%
See 3 more Smart Citations